Stakeholder Disparities in Islamic Financial Literacy and Financial Behavior: Evidence from a Pesantren Community - Hanif Noer Kholis; Sulhan (JOM, 2025)
Islamic financial literacy (IFL) is crucial for fostering responsible financial behavior in Muslim communities, yet empirical evidence from pesantren ecosystems remains limited. This study investigates the relationship between IFL and saving and investment behaviors among stakeholders at Pondok Pesantren Karangdurin. Using a quantitative approach, the study surveyed 120 respondents, comprising administrators, alumni, parents, and students, selected through stratified purposive sampling, and analyzed the data using descriptive statistics, correlation analysis, regression models, ANOVA, and post hoc Tukey HSD tests. Results reveal strong positive correlations between IFL and both saving (r = 0.47) and investment behaviors (r = 0.77). Regression analysis shows that IFL explains 22.15% of saving behavior and 59.23% of investment behavior variance. Significant differences are observed across stakeholder groups, with administrators demonstrating the highest literacy and behavioral scores. This study extends Islamic financial literacy behavior theory to a pesantren based, multi stakeholder context, providing novel empirical evidence on intra institutional disparities and supporting the design of differentiated, stakeholder-specific financial education interventions.